2018
DOI: 10.2807/1560-7917.es.2018.23.2.17-00852
|View full text |Cite
|
Sign up to set email alerts
|

Ongoing nationwide outbreak of Salmonella Agona associated with internationally distributed infant milk products, France, December 2017

Abstract: On 1 December 2017, an outbreak of Salmonella Agona infections among infants was identified in France. To date, 37 cases (median age: 4 months) and two further international cases have been confirmed. Five different infant milk products manufactured at one facility were implicated. On 2 and 10 December, the company recalled the implicated products; on 22 December, all products processed at the facility since February 2017. Trace-forward investigations indicated product distribution to 66 countries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
41
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(42 citation statements)
references
References 9 publications
1
41
0
Order By: Relevance
“…In China, a study based on the literature review estimate that the incidence of non-typhoidal salmonellosis was 626.5 cases per 100,000 persons (Mao et al, 2011 ; Pan et al, 2018a ; Yue et al, 2020 ). However, many studies have reported Salmonella as the responsible agent of many foodborne outbreaks in China and elsewhere (Wang et al, 2007 ; Cleary et al, 2010 ; Hedican et al, 2010 ; Le Hello et al, 2012 ; Guo et al, 2015 ; Moffatt et al, 2016 ; Jourdan-Da Silva et al, 2018 ). Currently, animals, in particular, poultry and eggs are considered to be the primary cause for salmonellosis and numerous other foodborne outbreaks (Gieraltowski et al, 2016 ; Keerthirathne et al, 2017 ; Biswas et al, 2019 , 2020 ; Yu et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…In China, a study based on the literature review estimate that the incidence of non-typhoidal salmonellosis was 626.5 cases per 100,000 persons (Mao et al, 2011 ; Pan et al, 2018a ; Yue et al, 2020 ). However, many studies have reported Salmonella as the responsible agent of many foodborne outbreaks in China and elsewhere (Wang et al, 2007 ; Cleary et al, 2010 ; Hedican et al, 2010 ; Le Hello et al, 2012 ; Guo et al, 2015 ; Moffatt et al, 2016 ; Jourdan-Da Silva et al, 2018 ). Currently, animals, in particular, poultry and eggs are considered to be the primary cause for salmonellosis and numerous other foodborne outbreaks (Gieraltowski et al, 2016 ; Keerthirathne et al, 2017 ; Biswas et al, 2019 , 2020 ; Yu et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…1,4,[5],12:i:- isolates recovered in the present study showed an absence of H 2 S production, which is a rare phenotypic feature among Salmonella, regardless of the serotype. However, non-H 2 S-producing Salmonella has been reported in the last few years in emerging or outbreak-associated strains recovered from diverse food and human sources worldwide ( Table 2 ) [ 6 , 56 , 57 ]. Until now, two molecular mechanisms were reported as being responsible for the inability to produce H 2 S in diverse Salmonella serotypes (e.g., Aberdeen, Choleraesuis, Infantis, Senftenberg, Typhimurium, and 1,4,[5],12:i:-) and sources ( Table 2 ) [ 58 , 59 , 60 ].…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, asymptomatic pigs represent a constant risk of Salmonella transmission to humans and other animal species (1,22). Pork meat has been considered one of the major food products of animal origin responsible for Salmonella transmission to humans in diverse countries, including industrialized ones (22)(23)(24), being responsible for outbreaks in humans, as described in the literature for S. Agona (25), S. Senftenberg (26), and S. Schwarzengrund (27).…”
Section: Introductionmentioning
confidence: 99%
“…Pork meat has been considered one of the major food products of animal origin responsible for Salmonella transmission to humans in diverse countries, including industrialized ones ( 22 24 ), being responsible for outbreaks in humans, as described in the literature for S . Agona ( 25 ), S . Senftenberg ( 26 ), and S .…”
Section: Introductionmentioning
confidence: 99%